PENERAPAN STRATEGI LEARNING START WITH A QUESTION (LSQ) UNTUK MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR PESERTA DIDIK KELAS X AP2 SMK TRIATMA JAYA BADUNG TAHUN PELAJARAN 2013/2014 - Ni Nyoman Parmithi; Alexius Wahidin (Emasains : Jurnal Edukasi Matematika dan Sains, 2016)
Implementation of the Strategy Learning Start with a Question (LSQ ) to Enhance the Activity and Learning Achievement of Grade X AP2 SMK Triatma Jaya Badung Academic Year 2013-2014. The purpose of this study was to determine whether the application of learning strategies Learning Start With A Question can increase the activity and achievements of learners class Triatma Jaya Badung XAP2 vocational school year 2013/2014. This type of research is a classroom action research (PTK), with research subjects all students of class X AP 2 SMK Triatma Jaya Badung totaling 28 people. The method used in the processing of the data is descriptive statistical analysis method, while the learners' learning activity data collected by the observation sheet and analyzed using descriptive statistics. This esearch was conducted in two cycles, with the average yield learning activities obtained at the beginning of 14.53 observation study continued to the first cycle with the use of active learning model type LSQ and gained an average of 15.25 and further activity is aximized at cycle II with an average gain of 16.42 and categorized active. By applying active learning model types Learning Start With A Question (LSQ) in the first cycle and the average results obtained 76.78, 76.78% absorption and classical completeness of 82.1%, and if converted into PAP ( valuation benchmark reference) categorized quite good, while to maximize the action in the first cycle, proceed to the second cycle and gained an average of 85.12, 85.12% absorption and classical completeness of 92.8%.